Dieting among Thai adolescents: Having friends who diet and pressure to diet - Randy M. Page (2018)
The purpose of this study was to assess dieting behavior, the number of friends who diet, and number of friends who pressure to go on a diet among a sample of 2,519 Thai adolescents. More than half of the girls (52.2%) and over one-fourth of boys (28.0%) reported going on a diet in the past 30 days. Dieting among friends was very common with only 14.2% of girls and 34.3% of boys saying none of their friends dieted. Results also showed significant associations between 1) number of friends who diet and 2) number of friends who pressure to diet with dieting behavior, body mass index (BMI), weight satisfaction, perceived body fatness, effort to look like people in the media, and frequency of thinking about wanting to be thinner in girls. In addition, several of these associations for boys were significant. The role of BMI in these relationships was also explored. ©2007, Editrice Kurtis.